Equity in discourse for mathematics education : theories, practices, and policies - Herbel-Eisenmann, Beth.; Choppin, Jeffrey; Wagner, David; Pimm, David (b, 2012)
This book explores the connection between the ways people speak in mathematics classrooms and their opportunities to learn mathematics. The words spoken, heard, written and read in mathematics classrooms shape students' sense of what mathematics is and of what people can do with mathematics.
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching; Interaction analysis in education; Discourse analysis